2023
DOI: 10.1186/s13068-023-02260-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of non-food corn biomass to polyol esters of fatty acid and single-cell oils

Abstract: Background Lignocellulose is a valuable carbon source for the production of biofuels and biochemicals, thus having the potential to substitute fossil resources. Consolidated bio-saccharification (CBS) is a whole-cell-based catalytic technology previously developed to produce fermentable sugars from lignocellulosic agricultural wastes. The deep-sea yeast strain Rhodotorulapaludigena P4R5 can produce extracellular polyol esters of fatty acids (PEFA) and intracellular single-cell oils (SCO) simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…6 with a single PFK gene, which have the potential to serve as biorefinery cell factories utilizing glucose as a carbon resource. Notably, Rhodotorula paludigena P4R5 has demonstrated the ability to accumulate 23.5 g/L polyol esters of fatty acids from 140 g/L glucose [ 44 ]. Moesziomyces aphidis XM01 can accumulate 53.9% intercellular lipid from 80 g/L glucose [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 with a single PFK gene, which have the potential to serve as biorefinery cell factories utilizing glucose as a carbon resource. Notably, Rhodotorula paludigena P4R5 has demonstrated the ability to accumulate 23.5 g/L polyol esters of fatty acids from 140 g/L glucose [ 44 ]. Moesziomyces aphidis XM01 can accumulate 53.9% intercellular lipid from 80 g/L glucose [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fermentable sugars from lignocellulosic wastes have been used to produce intracellular single-cell oils and extracellular polyol ester of fatty acids (PEFA). For this purpose, Liu et al [82] reported that Rhodotorula paludigena is capable of co-utilizing xylose and glucose. The regulation of the sugar metabolism pathway for different monosaccharide strains can produce PEFA.…”
Section: Production Of Lipid Products and Biosurfactantsmentioning
confidence: 99%
“…The regulation of the sugar metabolism pathway for different monosaccharide strains can produce PEFA. Further, the use of corncob or corn stover hydrolysates to replace pure sugars in fermentation led to high yields, indicating the facile transformation of non-food corn waste to high-value lipids and glycolipids [82]. Zheng et al [166] reported simultaneous saccharification and fermentation of cassava residues for non-toxic and biodegradable rhamnolipid biosurfactant production.…”
Section: Production Of Lipid Products and Biosurfactantsmentioning
confidence: 99%